Analisis Asosiasi Data Penjualan Produk Mega Baja Cipondoh Kota Tangerang Menggunakan Algoritma Fp-Growth - Kamelia Faridah; Nining Rahaningsih; Raditya Danar Dana (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2024)
Mega Baja Cipondoh, a construction material store in Tangerang, is experiencing suboptimal sales and revenue decline. This research addresses the issue through Fp-Growth algorithm application in sales data analysis using RapidMiner. With a minimum Support of 0.002, minimum Confidence of 0.8, and lift value of 1, six significant association rules are identified. For instance, 10.4% of transactions involve purchasing both Hollo Galvanis and Pipa Galvanis. Customers buying Hollo Galvanis have a 9.6 times higher chance of also purchasing Pipa Galvanis, achieving a 100% success rate. Implementation of these findings is expected to enhance Mega Baja Cipondoh's sales strategy, optimize sales, and improve customer satisfaction, laying the groundwork for future developments in construction material sales data analysis.